Leveraging drones, digital tools, and near-real time data for enhanced decision making by smallholder farmers - Jardinero, Benedict (International Rice Research Institute, 2024)
Presented at the 11th National Congress and 2024 Philippine Agriculturists’ Summit on July 4, 2024, this talk highlights ongoing research by the CGIAR Digital Innovation Initiative and the International Rice Research Institute (IRRI) to revolutionize agriculture through digital tools. With a focus on smallholder farmers, the presentation explores how emerging technologies—such as drones, advisory platforms, and data-driven decision-making—can enhance productivity, sustainability, and inclusivity in the Global South. It also addresses critical challenges, including the digital divide and limited access to actionable insights, emphasizing the need for research-based solutions to bridge these gaps and ensure equitable agricultural advancements.